Review of Cancer among Circumpolar Indigenous Peoples. Summary Report to the Sustainable Development Working Group. - Young, Kue (Sustainable Development Working Group (SDWG), 2015)
Draft version of Prof. Kue Young's "Review of Cancer among Circumpolar Indigenous Peoples. Summary Report to the Sustainable Development Working Group". Submitted by the Arctic Council working group Sustainable Development Working Group to the Arctic Council's Senior Arctic Officials meeting in Whitehorse, Canada, March 4-5 2015. NOTE: This is a draft version and not the final summary report. The final version of the summary report can be found among the documents from the Ministerial Meeting in Iqaluit 2015, or via this link: https://oaarchive.arctic-council.org/handle/11374/434.